Tata Kelola Rekam Medis Elektronik untuk Menentukan 3 Besar Penyakit di Rumah Sakit Gigi dan Mulut Bandung dengan Metode Agile - Ferdiansyah, Moehammad Rizky; Syahidin, Yuda; Yunengsih, Yuyun (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Limited knowledge Diseases and medical conditions are constantly evolving, and sometimes physicians may not update their knowledge of recent changes in ICD-10 (International Statistical Classification of Diseases) code classifications or other coding systems in use. This may lead to errors or discrepancies in code assignment, the aim of which is to provide global standards in the documentation and reporting of health events. The ICD coding system is essential in the healthcare field because it allows medical professionals to effectively record, analyze, analyze patient data, as well as create global epidemiological statistics. Based on research, creating solutions to problems that occur. Therefore, researchers created an information system with the aim of making it easier for medical records officers to record and determine the 5 major diseases which will later be reported to the Head of Medical Records, such as manual searches, increasing officer workload, and entering data into Microsoft Excel to create a list. the top three diseases are still a long process two of the many drawbacks of indexing. The method proposed to overcome this problem is to apply the development method with Agile Software Development by involving key stakeholders. The features that can be implemented in this software include forms for collecting patient data. This system helps in efficient management of medical files by facilitating simple access to patient data and reducing the chances of human error and loss of information. Keywords: Information system design; medical record reporting; software development using the Agile Software Development method